Attendance in physical education classes, sedentary behavior, and different forms of physical activity among schoolchildren: a cross-sectional study - Gilmar Mercês de Jesus; Raphael Henrique de Oliveira Araujo; Lizziane Andrade Dias; Anna Karolina Cerqueira Barros; Lara Daniele Matos dos Santos Araujo; Maria Alice Altenburg de Assis (BMC, 2022)
Abstract Background Attendance in physical education classes (PE) helps young people to achieve the physical activity recommendations and to reduce their exposure to sedentary behavior. However, the association between PE attendance and the daily frequency of specific forms of physical activity is less known. The current study analyzed the association between weekly attendance in PE and daily frequencies of different forms of physical activity (active play, non-active play, structured physical activity), and overall daily frequencies of physical activity (PA) and sedentary behaviors (SB) among schoolchildren. Methods Cross-sectional study with schoolchildren from second to fifth grade of 11 public schools (n = 2,477; 9.1 ± 1.38-y-old; 53.2% girls; 17.5 ± 3.5 kg/m2) in Feira de Santana (Northeast Brazil). PA, SB, and attendance in PE were self-reported using a previously validated on-line questionnaire based on the previous day's recall (Web-CAAFE). Multiple Binomial Negative regression modeling was carried out to analyze the association (Prevalence Rate: PR) between weekly attendance in PE (0/week, 1/week, ≥ 2/week) and frequencies of active play, non-active play, and structured physical activity, with adjustments by age, school shift, and BMI z-scores. Regression models analyzing overall PA also included adjustments by household chores. Results Attendance in PE ≥ 2/week was associated with higher frequencies of active play (girls: PR = 1.40, 95%CI = 1.11-1.78; boys: PR = 1.49, 95%CI = 1.15-1.94) and structured physical activity (girls: PR = 2.11, 95%CI = 1.31-3.40; boys: PR = 4.33, 95%CI = 1.63-11.52). Higher attendance in PE (≥ 2/week) was associated with high overall PA (girls: PR = 1.31, 95%CI = 1.06-1.62; boys: PR = 1.42, 95%CI = 1.14-1.77) and low SB (girls: PR = 0.80, 95%CI = 0.71-0.90; boys: PR = 0.81, 95%CI = 0.68-0.97). Attendance in PE 1/week was also associated with a lower frequency of daily SB among girls (PR = 0.73, 95%IC = 0.64-0.84) Conclusion Higher weekly attendance in PE was associated with higher frequencies of active play, structured physical activity, higher overall PA, and lower SB among both girls and boys.